2022
DOI: 10.2166/wcc.2022.208
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential impacts of climate change on streamflow in the data-scarce Upper Ruvu River watershed, Tanzania

Abstract: This study assessed the impacts of climate change on streamflow in the data-scarce Upper Ruvu River watershed (URRW). The Long Ashton Research Station Weather Generator (LARS-WG) was employed for generating the future ensemble-mean climate scenario based on six global circulation models (GCMs), under two representative concentration pathways (RCPs: RCP4.5 and RCP8.5). The future projections were made in two periods (2041–2060 and 2081–2100), and the baseline period (1951–1978) was used as a reference. The wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…Thus, in this study to predict the impact of changing climate on the SF for the future period, three GCMs (ACCESS-CM2, BCC-CSM2-MR, and CanESM5) from CMIP6 were employed under three different scenarios (ssp245, ssp370, and ssp585). Additionally, the findings of this study agree with those of previous related studies [57,58].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, in this study to predict the impact of changing climate on the SF for the future period, three GCMs (ACCESS-CM2, BCC-CSM2-MR, and CanESM5) from CMIP6 were employed under three different scenarios (ssp245, ssp370, and ssp585). Additionally, the findings of this study agree with those of previous related studies [57,58].…”
Section: Discussionsupporting
confidence: 93%
“…The most sensitive parameters reported in this study are the Curve Number, lag time and the flood wave travel time factors for flood peak, while only the Curve Number parameter was found to be sensitive for flood runoff volume. These findings could be compared to other studies that reported the percent impervious followed by the groundwater coefficient to be the most sensitive parameters [82,83]. Ref.…”
Section: Discussionmentioning
confidence: 73%
“…However, few have performed the statistical downscaling in Tanzania for hydrological impact assessment (Ayugi et al, 2021;Shagega et al, 2019;Tibangayuka et al, 2022;Wambura, 2014). However, most of these studies were carried out at the regional level, which are less relevant for planning and managing water resource infrastructures at the catchment scale (Pachauri & Meyer, 2014).…”
Section: Climate Change and Climate Downscalingmentioning
confidence: 99%